Analytical capillary isotachophoresis after 50 years of development: Recent progress 2014–2016. Issue 1 (29th August 2016) - Malá, Zdena; Gebauer, Petr; Boček, Petr
Abstract : This review brings a survey of papers on analytical ITP published since 2014 until the first quarter of 2016. The 50th anniversary of ITP as a modern analytical method offers the opportunity to present a brief view on its beginnings and to discuss the present state of the art from the viewpoint of the history of its development. Reviewed papers from the field of theory and principles confirm the continuing importance of computer simulations in the discovery of new and unexpected phenomena. The strongly developing field of instrumentation and techniques shows novel channel methodologies including use of porous media and new on‐chip assays, where ITP is often included in a preseparative or even preparative function. A number of new analytical applications are reported, with ITP appearing almost exclusively in combination with other principles and methods.